(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Rare-earth-oxides (REOs) in impressive consideration in view of their potential application in catalyst and optoelectronic gadgets. REOs have promising optical, electrical and chemical properties. They are described by the progressive filling of the 4f level of their electronic arrangement. Among REOs, praseodymium oxide is a significant REO material utilized as catalyst, oxygen storage components and material for higher electrical conductivity. Praseodymium oxide includes unique highlights inside the arrangement of the REOs. It structures homologous a progression of oxides with variable valence states. This has the most astounding oxygen ion mobility inside the arrangement of lanthanide oxides, on account of the assortment of stable phases, which empowers quick changes in the oxidation state of praseodymium. Different methods have been embraced for the synthesis of phase pure praseodymium oxide nanoparticles like solid state synthesis, hydrothermal, microwave assisted synthesis, sol-gel, and so on. Among the above mentioned, the wet chemical approach is a simple, versatile method to prepare phase pure, controllable nanoparticles with high return. The prepared particles are exposed to post synthesis processes and characterized for their basic morphological studies.